Royalists, radicals, and les Miserables : France in 1832 - Martone, Eric (Cambridge Scholars Publishing, 2013)
The year of 1832 marked a turning point in France as the country struggled to find its way in the wake of the French Revolution. Following the Revolution of 1830, Legitimists, supporters of the recently ousted Bourbon dynasty’s claim to the throne, continued to plot against King Louis-Philippe and his “July Monarchy.” In early 1832, after failing to launch a coup in Southern France, Legitimists plotted an unsuccessful uprising in the Vendée, a region in Western France that had supported the royalist cause during the French Revolution. The Duchesse de Berry led the rebellion in the hopes of placing her son, the Bourbon heir, on the French throne. The revolt marked the last attempt by the Bourbons to retake the throne by force and helped solidify the end of the Bourbon dynasty. During the cholera outbreak, which also spread throughout France in 1832, lower income areas suffered higher losses to the disease, for they were more likely to have contaminated water supplies. The lower classes spread rumors that the outbreak was an elitist plot to subdue the masses and the epidemic exacerbated class tensions. Meanwhile, conditions in France continued to be characterized by violence during the early 1830s as Louis-Philippe attempted to establish his regime’s authority. The most significant of these uprisings was the republican-dominated June Revolution of 1832. Victor Hugo and other contemporaries perceived the barricades of June as natural extensions of the cholera epidemic, or the “political continuation of a biological crisis.” The sad fate of the uprising, however, prompted republicans to regroup and develop new strategies for success. As a whole, then, 1832 helped solidify the end of the Bourbon monarchy and class identities, and was a crucial moment in the (re)organization and growing solidification of French republicanism that paved the way for the Revolution of 1848.